1993
DOI: 10.1007/bf01309551
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction-mediated cloning and in vitro translation of the genes coding for the structural proteins of hog cholera virus

Abstract: After amplification by PCR, the 5' region of the genome of hog cholera virus (HCV) strain Alfort 187 was cloned and sequenced. The nucleotide and deduced amino acid sequences were compared with the ones of other pestiviruses. By in vitro translation experiments we were able to demonstrate the protease activity of the p 20 protein of HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In the present work, single nucleotide dif- (11,39), it cannot be excluded that some of the differences found between the clones analyzed were due to sequence heterogeneity in the original virus stock. Previous partial sequencing of the Alfort/ 187 genome in at least two laboratories had suggested that the nucleotide sequence published for Alfort Tübingen (25) was only distantly related to the sequence of Alfort/187 (14,32,37,38), a clone of the original Alfort strain (1,6). This is clearly confirmed by the sequence data presented in this work, which revealed an overall nucleotide sequence identity of 86.2% between the Alfort Tübingen sequence (25) and the Alfort/187 sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, single nucleotide dif- (11,39), it cannot be excluded that some of the differences found between the clones analyzed were due to sequence heterogeneity in the original virus stock. Previous partial sequencing of the Alfort/ 187 genome in at least two laboratories had suggested that the nucleotide sequence published for Alfort Tübingen (25) was only distantly related to the sequence of Alfort/187 (14,32,37,38), a clone of the original Alfort strain (1,6). This is clearly confirmed by the sequence data presented in this work, which revealed an overall nucleotide sequence identity of 86.2% between the Alfort Tübingen sequence (25) and the Alfort/187 sequence.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of animal experiments performed at our institute and according to the criteria of van Oirschot (46), Alfort/187 must be classified as a moderate-virulent strain (our unpublished data). Data obtained previously from partial sequencing of the Alfort/187 genome (14,32,37,38) indicated that Alfort Tübingen and Alfort/187 were only distantly related strains.…”
mentioning
confidence: 95%
“…In addition to the aforementioned published nucleic acid sequences the multiple alignment for the gp fragments included sequence from the Alfort 187 (Muyldermans et al, 1993) and the Weybridge (Yu et al, 1993) strains of CSFV. All the sequences showed a high level of conservation with variation occurring mainly at the wobble bases.…”
Section: Relationships Between Italian Csfvsmentioning
confidence: 99%
“…Several PCRs for the detection of CSFV have been reported. 8,12,15 Of these, no PCR assay was applied to test semen samples for the presence of CSFV. The amount of CSFV nucleic acid present in semen appears to be low because it could only be detected after the seminested RT-PCR.…”
Section: Discussionmentioning
confidence: 99%